Healing Architecture: exploring own mind and emotions in inner city of Seoul - Kim, Min-Joo (My University, 2017)
The world is changing fast in every ﬁ eld of technology. As technology rapidly develops, humans need to adapt to excessive learning and work loads, in order to meet the current society demands. Extreme stress accumulates, and nega vely aﬀ ects peoples’ physical health. Stress causes many mental illnesses as well. However, many people avoid going to mental hospitals, because of the s gma or the nega ve stereotype associated with mental illness. Therefore, people try to relieve their stress in physical ways by exercising, travelling, or partaking in other leisure ac vi es. They use psychology, religion, therapy, or medita on to relieve their stress. Today, in South Korea, many people work long hours into the night and on the weekend. Many of these people cannot aﬀ ord treatments that relieve stress, because they do not have the me or the money. Most South Koreans spend their days in their work space. In a highly compe ve work environment and networking environment created by social media, the South Korean people lose self-esteem. People blame the social structure and hierarchy for the defec ve working culture. People get depressed or lose their self-esteem by being submissive, rather than fully expressing their opinions especially regarding the ruling class. As a result, many people plan or consider emigra ng. South Koreans, o en forget or lose their iden es and essen al quali es. This document suggests that an urban medita on centre should be built close to the business districts in South Korea. People could visit the centre whenever they need a break from their tough working environment. Visitors to the medita on centre would use all their senses to feel alive, and to realise and reaﬃ rm their existence. Through this sensory experience, they would also be able to meditate and ﬁ nd inner peace. This report aims to research how architecture can help to release stress in an urban context and how this space could enhance peoples’ various sensory experiences. Healing architecture explores all the human senses using the theory of phenomenology
Thesis is submitted in partial fulfilment for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2017
Keywords: City planning--Korea (South); Architecture--Korea (South); Seoul (Korea); Meditation--Therapeutic use